The Canonical E2Fs Are Required for Germline Development in Arabidopsis - Yao, Xiaozhen; Yang, Huidan; Zhu, Yingxiu; Xue, Jingshi; Wang, Tianhua; Song, Teng; Yang, Zhongnan; Wang, Shui (Frontiers in Plant Science, 2018)
A number of cell fate determinations, including cell division, cell differentiation, and programmed cell death, intensely occur during plant germline development. How these cell fate determinations are regulated remains largely unclear. The transcription factor E2F is a core cell cycle regulator. Here we show that the Arabidopsis canonical E2Fs, including E2Fa, E2Fb and E2Fc, play an essential role in plant germline development. The e2fa e2fb e2fc (e2fabc) triple mutant is sterile, although its vegetative development appears normal. On the one hand, the e2fabc microspores undergo cell death during pollen mitosis. Microspores start to die at the bicellular stage. By the tricellular stage, the majority of the e2fabc microspores are degenerated. On the other hand, a wild type ovule often has one megaspore mother cell (MMC), whereas the majority of e2fabc ovules have two to three MMCs. The subsequent female gametogenesis of e2fabc mutant is aborted and the vacuole is not formed in the embryo sac. Analysis of transmission efficiency showed that the canonical E2Fs from both male and female gametophyte are essential for plant gametogenesis. Our study reveals that the canonical E2Fs are required for plant germline development, especially the pollen mitosis and the archesporial cell (AC)-MMC transition.